Dualisme Prosedur Eksekusi Jaminan Fidusia: Pada Undang-Undang No.42 Tahun 1999 Pasca Putusan Mahkamah Konstitusi No. 18/PUU-XVII/2019 - Amirah Luthfiyyah (Jurnal Hukum Lex Generalis, 2026)
The Constitutional Court Decision Number 18/PUU-XVII/2019 has brought fundamental changes to the implementation of fiduciary security execution as regulated under Law Number 42 of 1999. The executorial power of the Fiduciary Security Certificate can no longer be exercised directly through parate execution, but must instead be based on an agreement regarding the occurrence of default or pursued through legal mechanisms that ensure the protection of the debtor’s rights. This study analyzes the dualism of fiduciary execution procedures under Law Number 42 of 1999 in relation to the Constitutional Court Decision Number 18/PUU-XVII/2019 from the perspective of legal certainty, employing a normative legal research method through statutory and conceptual approaches. The findings indicate a shift in the meaning of executorial power, the emergence of dual execution procedures, and the positioning of default as a threshold requirement for the implementation of execution. This study emphasizes the necessity of harmonizing the interpretation of Article 15 and Article 29 in order to achieve legal certainty and a balanced protection for both creditors and debtors